Perancangan UI/UX Pada SIMKLINIK Bagian Pendaftaran Di Klinik Jaya Kusuma Husada - Maulana, Moh; Anugrahanti, Wisoedhanie Widi (Akademi Perekam dan Informasi Kesehatan Imelda, 2026)
At the Jasa Kusuma Husada Clinic, patient registration management still uses a manual, paper-based system. The use of this system has the potential to cause inefficiencies in service time, patient identification errors, and data duplication. Based on these problems, the researcher designed the user interface (UI) and user experience (UX) on the registration section of the clinic management information system (SIMKLINIK) at the Jaya Kusuma Husada Clinic. The method used in this study was Research and Development (R&D). The results of this study, the design aspects of the User Interface (UI) and User Experience (UX) in the registration section of the clinic management information system (SIMKLINIK), were observed on 22 assessment indicators covering aspects of navigation, icon clarity, design consistency, and flexibility of use, showing that they meet the expected standards. In conclusion, the UI / UX design for the registration section of SIMKLINIK has been prepared based on the results of the user needs analysis